Reply—On “Rankings from Round-Robin Tournaments” by Professor Michael Stob - Goddard, Stephen (Management Science, 1985)
Reply to Stob, M. 1985. Note—Rankings from Round-Robin tournaments. Management Sci. 31 (9, September) 1191–1195.